A Study on the Impact of the National Technical Regulation on Fire Safety for Buildings and Structures on Airport Construction Projects in Vietnam (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In the context of Vietnam’s accelerated development of aviation infrastructure, airport construction projects-particularly airport terminal buildings-are increasingly characterized by large-scale facilities, open architectural layouts, extensive multi-level atrium spaces and highly integrated technical systems. The promulgation of the National Technical Regulation on Fire Safety for Buildings and Structures (QCVN 06:2022/BXD) and its Amendment No. 1:2023 has contributed to raising the overall level of fire safety for buildings and structures. However, it has also created a number of “bottlenecks” when applied to highly specialized facilities such as airports. This paper employs a policy and regulatory analysis approach, typical case studies across the project life cycle, and comparative analysis with international standards, including International Civil Aviation Organization (ICAO) Doc 9137 Part 1 and relevant National Fire Protection Association (NFPA) standards applicable to airport facilities. The findings indicate that the impacts of QCVN 06:2022/BXD are most significant in four major areas: (i) master planning and fire service access; (ii) architectural design of terminal buildings (access routes, roof access, and open spaces); (iii) fire compartmentation, egress, and smoke control in large spaces; and (iv) approval procedures, acceptance processes, and management of design and functional changes. Based on these findings, the paper proposes a set of solutions, including the development of an “airport annex” guidance document for QCVN 06, the establishment of a Performance-Based Design (PBD) framework with transparent criteria, the resolution of inter-agency conflicts through coordination mechanisms, and the harmonization of Aircraft Rescue and Firefighting (ARFF) capability requirements in line with ICAO standards.